The impact of linguistic concordance and the active offer of French language services on patient satisfaction - Timony, Patrick; Gauthier, Alain; Wenghofer, Elizabeth; Hien, Amelie (Diversity of Research in Health Journal / Revue de la diversité de la recherche en santé, 2022)
Communication is essential to providing quality primary care. Linguistic concordance between patients and physicians has been linked to improved health outcomes and greater patient satisfaction. Although Canadian Francophones often struggle to access linguistics concordant health services, the concept of the active offer of French Language Services (FLS) has emerged as a means of ensuring the availability of such services and improving the francophone patient experience. However, the impact of language concordance and the active offer of FLS on patient satisfaction among Ontario Francophones remain largely unknown. Patient satisfaction surveys were collected as part of a continuing education program targeted at family physicians in Northeastern Ontario. Participating physicians distributed patient surveys consisting of select patient satisfaction questions from the Physicians Achievement Review (PAR) and select questions from the Active Offer of French Language Services in Minority Context Measure. Valid surveys were received from 235 patients. Just under half of these (44%) identified as Francophones, 62.6% had a French-speaking family physician; however, only 17.2% reported regularly speaking in French with their family physician. As hypothesized, there was a consistent tendency for Francophones who experience stronger linguistic concordance with their family physician to report higher satisfaction scores. Francophones who regularly speak French with their family physicians were more satisfied ( = 4.63) than those who rarely/never speak French ( = 4.29, F(1; 83) = 4.852; p < 0.05). There was also a statistically significant interaction between the patients' language of preference and the service language. Francophones who prefer French and regularly speak it with their family physician (linguistic concordance; adj= 4.82) were significantly more satisfied than those who prefer French yet rarely/never speak it (linguistic discordance; adj= 4.06, F(1; 75) = 11.950; p < 0.001). Furthermore, a positive correlation between patient satisfaction and the active offer was observed in Francophones (r = 0.49, p<0.001). The present findings provide evidence of the impact of linguistically adapted health care services on the satisfaction of Ontario Francophones and suggest that patient satisfaction may be improved through the active offer of FLS. A larger and more diverse sample is required to confirm these findings.

Expérience de francophones en Ontario chez leur médecin de famille : concordance et discordance linguistique - Jutras, Chloé; Gauthier, Alain P.; Timony, Patrick E.; Côté, Daniel; Kpazaï, Georges (La Revue de la Diversité de la Recherche en Santé, 2020)
Abstract : Improving health and health care can be achieved efficiently by improving the patient experience. This study’s main objective was to capture and understand the Francophone patient experience during a visit to their family physician’s office and examining the impact of linguistic concordance or discordance on this experience. Data collection method was inspired by the first two steps of the Experience Based Design approach (EBD), six focus groups were conducted in strong French communities of Northern Ontario in which a total of twenty-nine Francophones described their experience of a visit to their family physicians’ office. The Francophone patient experience is characterized by many emotions, several of which result from the presence of linguistic concordance or discordance with the physician. Linguistic discordance in a primary care setting elicits a less favorable patient experience in terms of emotions associated with comfort, accessibility, security and personal aptitude. Actively offering French language services, being mindful of patient language preferences regardless of apparent bilingualism and providing a bilingual environment in the family physician’s office (e.g. signage, forms) would favor a positive patient experience for Francophones in Ontario.

Linguistic factors and COVID-19 outcomes among long-term care residents in Ontario, Canada - Reaume, Michael; Batista, Ricardo; Imsirovic, Haris; Bjerre, Lise; Kendall, Claire E.; Bouchard, Louise; Gauthier, Alain P.; Landry, Josette-Renée; Chomienne, Marie-Hélène; Muray, Mwali; Hsu, Amy; Prud'homme, Denis; et al. (BMC Geriarics, 2025)
Abstract Background The COVID-19 pandemic disproportionately affected frail individuals, especially those living in long-term care (LTC) homes. This study examined the role of linguistic factors on COVID-19 related outcomes in LTC homes. Methods We performed a population-based, retrospective cohort study of residents living in LTC homes in Ontario, Canada who were diagnosed with COVID-19 between March 31, 2020 and March 31, 2021. Resident language, obtained from LTC assessments, was used to classify residents into one of the three linguistic groups: Anglophone (English), Francophone (French), and allophone (other language). Language of the LTC home was determined using a person-time representation of the languages spoken by residents within each LTC home. We defined LTC facilities as French homes when Francophone residents contributed more than 25% of the person-days, and allophone homes when allophone residents contributed more than 50% of the person-days. Residents whose language corresponded to the language of the LTC home in which they were living were said to have received language-concordant care, while all other residents were said to have received language-discordant care. The outcomes of this study were ED visits, hospitalizations, and mortality within 90 days. Results We included a total of 26,829 LTC residents (20,315 Anglophones, 1,032 Francophones, and 5,482 allophones) living in 572 LTC homes (502 English, 28 French, 42 allophone) who were diagnosed with COVID-19. LTC residents who lived in language-discordant homes were more likely to have ED visits (adjusted HR 1.12, 95% CI 1.01–1.25) and hospitalizations (adjusted HR 1.15, 95% CI 1.02–1.29) when compared to LTC residents who lived in language-concordant homes. Residents-facility language discordance was not associated with overall mortality (adjusted HR 1.00, 95% CI 0.91–1.10) or in hospital mortality (adjusted HR 1.04, 95% CI 0.88–1.23). Conclusion Residents living in language-discordant LTC facilities experienced more ED visits and hospitalizations following diagnosis of COVID-19. The findings of this study highlight the importance of providing frail, vulnerable individuals with linguistically concordant care.

Disparities in COVID-19 infection rates across linguistic groups in long-term care homes in Ontario, Canada - Batista, Ricardo; Fitzgerald, Michael; Reaume, Michael; Kendall, Claire E.; Bjerre, Lise M.; Mahdavi, Roshanak; Imsirovic, Haris; Gauthier, Alain P.; Landry, Josette-Renée; Chomienne, Marie-Helene; Hsu, Amy; Bouchard, Louise; et al. (BMC Public Health, 2026)
Background The COVID-19 pandemic has had a disproportionate impact on residents of long-term care facilities or nursing homes, characterized by significantly higher infection and mortality rates than in the general population. Previous research has highlighted significant disparities in COVID-19 outcomes, particularly among ethnic minorities. This study examines the association between belonging to a minority language community and COVID-19 infection rates in LTCFs in Ontario, Canada, at both the individual and facility levels. Methods We conducted a population-based retrospective cohort study of 85,367 LTC home residents in Ontario between January 15, 2019, and March 30, 2020, which we followed until March 31, 2021, using data from the Continuing Care Reporting System. We defined resident language (obtained from routine assessments in nursing homes) as English (Anglophone), French (Francophone), or other (Allophone), and we calculated a weighted average of languages spoken by residents in each LTC facility to determine the linguistic environment of the LTC facility. We calculated incidence rates of COVID-19 for each linguistic group, and we fitted multilevel logistic regression models to assess the main factors influencing the risk of COVID-19 infection, to account for individual-level and facility-level linguistic factors. Results The overall incidence of COVID-19 was 14.8%. The incidence of COVID-19 was higher among Allophones (23.6%) compared to Anglophones (13.1%) and Francophones (12.2%). Allophones in English homes (22.5%) showed significantly higher incidence rates compared to Anglophones (13.1%) and Francophones (11.0%) in these same homes. After adjusting for sociodemographic and clinical characteristics, the risk of COVID-19 remained significantly higher for Allophones compared to Anglophones (aOR 1.14, 95% CI 1.05–1.22), while residents living in language-discordant nursing homes had a non-significantly higher risk of COVID-19 (aOR 1.07, 95% CI 0.99–1.14). Conclusions Over the first two waves of the COVID-19 pandemic, the risk of COVID-19 infection in nursing homes was highest among residents whose primary language was a language other than English or French. The results of our study show that COVID-19 disproportionately affected populations living in minority linguistic communities. These findings may help informing public health interventions aimed at addressing the language barriers in long-term care in Ontario, and across Canada.